Fine-tuning the antigen sensitivity of CAR T cells: emerging strategies and current challenges - Harrer, Dennis Christoph; Li, Sin-Syue; Kaljanac, Marcell; Barden, Markus; Pan, Hong; Abken, Hinrich (Frontiers in Immunology, 2023)
Chimeric antigen receptor (CAR) T cells are “living drugs” that specifically recognize their target antigen through an antibody-derived binding domain resulting in T cell activation, expansion, and destruction of cognate target cells. The FDA/EMA approval of CAR T cells for the treatment of B cell malignancies established CAR T cell therapy as an emerging pillar of modern immunotherapy. However, nearly every second patient undergoing CAR T cell therapy is suffering from disease relapse within the first two years which is thought to be due to downregulation or loss of the CAR target antigen on cancer cells, along with decreased functional capacities known as T cell exhaustion. Antigen downregulation below CAR activation threshold leaves the T cell silent, rendering CAR T cell therapy ineffective. With the application of CAR T cells for the treatment of a growing number of malignant diseases, particularly solid tumors, there is a need for augmenting CAR sensitivity to target antigen present at low densities on cancer cells. Here, we discuss upcoming strategies and current challenges in designing CARs for recognition of antigen low cancer cells, aiming at augmenting sensitivity and finally therapeutic efficacy while reducing the risk of tumor relapse.